Pengembangan Media Pembelajaran Penyajian Data Berbasis QR-Code Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD - Karisma, Deni; Zainil, Melva (Universitas Negeri Padang, 2022)
This study aims at developing QR-Code-based data presentation learning media which are valid and practical to improve the learning outcomes of the fourth year elementary school students. This study used a research and development (R&D) model consisting of such stages as analysis, design, development, implementation, and evaluation. The subject of this study included 2 experts, 2 teachers and 26 students at class IV-B of SDN 15 Ulu Gadut, Padang. The instrument used in this study included expert validation sheets and questionnaires distributed to the teachers and students. The results indicate that (1) the use of QR-Code-based data presentation learning media to improve the learning outcomes of the fourth year elementary school students is valid according to the material expert and very valid according to the linguistic expert and media expert with the validity average of 95,41; (2) based on the response of the teachers and students, the use of QR-Code-based data presentation learning media to improve the learning outcomes of the fourth year elementary school students is very practical with the average of 95% and 88%.